Pengaruh Penambahan Tepung Tapioka Pada Pati Ubi Kayu (Manihot esculenta) Terhadap Pembuatan Plastik Biodegradable dan Karakterisasinya - Abdul Rahim; Rustam Musta (Indonesian Journal of Chemical Analysis (IJCA), 2019)
Research on Biodegradable Plastic Characterization of Cassava Wastes (manihot esculenta) Substitution of Tapioca Flour. As Biodegradable Plastics Base Material. This study aims to determine the ratio of cassava starch to tapioca starch which produces the best biodegradable plastic which is then used for testing the physical and mechanical properties of biodegradable plastic film using 5% acetic acid. Comparison of cassava starch with tapioca flour used is 1 : 1; 1 : 1,5; 1 : 2; 1 : 2,5; 1 : 3. The best plastics are obtained by comparison of cassava starch with tapioca flour is 1 : 3. The characteristics of biodegradable plastics include physical characteristics consisting of thickness with value 0,273 mm, 0,286 mm, 0,413 mm, 0,280 mm, dan 0,510 mm. While the mechanical characteristics consist of tensile strength with value 0,22138 MPa, 2,10724 MPa, 0,78896 MPa, 3,25933 Mpa, dan 0,508 Mpa. Percent lengthening with value 42%, 32,8%, 55,6%, 20%, dan 31,6%. Based on the result of research, it can be concluded that the value of thickness, percent elongation, and tensile strength are influenced by the comparative formula used.Keywords:  Biodegradable plastic, physical properties, mechanics, cassava starch, tapioca flour